Influence of Performance Health Social Insurance Security Administering Agency and Quality of Health Services on Community Satisfaction at DKI Jakarta Province - Wikandono Wikandono; Muh. Ilham; Khasan Effendy; Sampara Lukman (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
DKI Jakarta Provincial Government which oversees health service centers such as Class A, B, C, D Public Hospitals and Puskesmas has made efforts to improve the quality of services from various aspects, but BPJS beneficiaries are still heard complaining about differences in attitudes and service procedures with and without using BPJS Health. Meanwhile, important aspects of service that must be met by health service centers as BPJS partners are Tangibles, providing clean facilities, neat treatment rooms and the appearance of uniformed and neat health workers, as well as aspects of Assurance providing safe services, complete and capable medical records. provide information related to the actions taken. Referring to the description above, the researchers conducted an in-depth study through a study entitled The Effect of the Performance of the Social Security Administering Body (BPJS) on Health and the Quality of Health Services on Community Satisfaction, to be able to know clearly how big the influence is. This study aims to determine the effect of performance and quality on satisfaction. The research method uses quantitative research using a survey approach. The data collection technique used is by using a questionnaire distributed to respondents consisting of health workers and the community or patients as users of health services. From the results of the study, the coefficient of determination (R2 -adjusted = 0.561) means that 56.1% of the community satisfaction level is influenced by the performance of BPJS Kesehatan and the quality of health services and the remaining 43.9% is influenced by other variables not tested in this study.